2023
DOI: 10.3389/fpsyg.2023.1061027
|View full text |Cite
|
Sign up to set email alerts
|

The influences of mindfulness on high-stakes mathematics test achievement of middle school students

Abstract: Research has shown that mindfulness can reduce students' negative emotions associated with high-stakes tests and thereby improve test performance. This study explored the association between mindfulness-based intervention (MBI) and high-risk math test scores of middle school students, which is noticeably slim in the domain of mathematics education, through a mediating process involving math-specific test anxiety and math self-efficacy. Using data from a sample of 45 students, age 12–13, we found empirical supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…MBIs can teach children to become aware and let go of their anxiety without further rumination. Qualitative interviews after a MBI on mathematics anxiety in China confirmed that the participants observed fewer physiological manifestations of anxiety, less test-irrelevant worry, and fewer obstacles to solving mathematical problems while at the same time gaining more math self-efficacy 21 . Meta-analyses agree that MBIs contributed to improving children’s socioemotional functioning, which included anxiety, stress, emotion regulation, and internalizing behaviors 11 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…MBIs can teach children to become aware and let go of their anxiety without further rumination. Qualitative interviews after a MBI on mathematics anxiety in China confirmed that the participants observed fewer physiological manifestations of anxiety, less test-irrelevant worry, and fewer obstacles to solving mathematical problems while at the same time gaining more math self-efficacy 21 . Meta-analyses agree that MBIs contributed to improving children’s socioemotional functioning, which included anxiety, stress, emotion regulation, and internalizing behaviors 11 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 78%
“…A RCT evaluating a MBI with fourth and fifth graders demonstrated that mathematics grades improved as a trend when the IG was compared to an active control group (ACG) 20 . Zuo and Wang 21 confirmed that an audio-based MBI contributed to the improvement of eighth graders’ math performance in high-stakes testing in China. Correlational studies indicated moderate positive associations between self-reported mindfulness and mathematics performance in middle school students 22 .…”
Section: Introductionmentioning
confidence: 86%